2016
DOI: 10.3402/gha.v9.29433
|View full text |Cite
|
Sign up to set email alerts
|

Trends and determinants for early initiation of and exclusive breastfeeding under six months in Vietnam: results from the Multiple Indicator Cluster Surveys, 2000–2011

Abstract: BackgroundThere is strong evidence that breastfeeding (BF) significantly benefits mothers and infants in various ways. Yet the proportion of breastfed babies in Vietnam is low and continues to decline. This study fills an important evidence gap in BF practices in Vietnam.ObjectiveThis paper examines the trend of early initiation of BF and exclusive BF from 2000 to 2011 in Vietnam and explores the determinants at individual and contextual levels.DesignData from three waves of the Multiple Indicator Cluster Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 17 publications
11
20
0
1
Order By: Relevance
“…This association has also been observed in other studies done in Uganda, Nigeria and Vietnam [12,26,35]. The practice of separating the newborn from the mother immediately after caesarean delivery could partly explain this delay [36].…”
Section: Discussionsupporting
confidence: 79%
“…This association has also been observed in other studies done in Uganda, Nigeria and Vietnam [12,26,35]. The practice of separating the newborn from the mother immediately after caesarean delivery could partly explain this delay [36].…”
Section: Discussionsupporting
confidence: 79%
“…At times, family members were reported to place constraints on providing nutritious foods for children by bringing previously-established food regulations. These findings are in line with previous studies that show that familiar relationships play a central role regarding child feeding practices as families are important social environments within which food-related behaviours among infants and young children are developed (Bui et al 2016;Cashdan, 1994).…”
Section: Discussionsupporting
confidence: 92%
“…[28,44,49,52,69]. The negative impact of caesarean delivery on early breastfeeding has also been observed in the several studies [8,28,29,34,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Discussionmentioning
confidence: 95%
“…Several studies conducted in developing countries have identified a number of socio-economic and demographic factors associated with EIBF such as place of residence [27], education of parents [8,[27][28][29][30][31][32][33][34], birth order [8,27,[35][36][37][38][39], place of delivery [8], mode of delivery [8,28,29,34,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58], size of baby [8], use of antenatal care [8,28,42,44,53,[59][60]…”
Section: Introductionmentioning
confidence: 99%